Leaving unemployment for self-employment: a discrete duration analysis of determinants and stability of self-employment among former unemployed - Frank Reize (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2000)
The paper investigates the determinants and the success of self-employment among former unemployed. Self-employment has become an important re-employment opportunity during the last decade due to increasing subsidies. The econometric analysis is carried out using discrete hazard rate models on 14 waves of the German Socio-Economic Panel, covering the period from 1983 to 1996. I do not find any effects of unemployment duration on the transition from unemployment to selfemployment. Moreover, unemployed people entering self-employment have higher skills than the average of the unemployed population and self-employment seems to be more stable than paid-employment would have been because people face a lower risk of becoming unemployed again.
Keywords: 330; Selbstständige; Arbeitslosigkeit; Dauer; Schätzung; Deutschland